Perspective on selected sample on SDL in JAVA-an analysis of a learning module design for pre-evaluation purposes - Ibrahim, Zakir Hussain (2001)
The celebration of the new millennium is ancient history in this Information Age. The Y2K Bug came and went with not much as a passing breeze on an eventful day. However, with the coming of the new millennium we are faced with different challenges especially during this troubled time. Public institution is facing problems in giving training and education to its staff. Due to the lack of funding and other resources. Thus, they are facing serious dilemma over how to give their staff the appropriate training and consequently benefit their organisation as well as the well being of their staff. This problems is not foreign to KUiTTHO as one of the emerging college university in Malaysia. Therefore, this research attempts to provide alternatives to KUiTTHO in providing it's staff. With the alternative provided KUiTTHO will be able to provide a better quality education to it's students and increase the professionalism within its campus of academicians and educators.